How do reputation, brand image affect the attraction of talent in the hospitality industry - Monteiro, Maria Carlota da Franca Taborda (2023)
This thesis addresses a challenge proposed by InterContinental Lisbon Hotel, intending to improve its human resources practices, focusing specifically on talent attraction. The study starts by setting the socioeconomic context of the industry and by making an overview of the hotel, followed by an exploration of factors influencing talent attraction, such as corporate reputation and brand image, acknowledging their critical role in shaping candidates' perceptions and career decisions. Through comprehensive methodologies including surveys and interviews, insights are gathered to understand the complex activities of talent attraction. The research also examines InterContinental Lisbon's approach to recruitment and internship programs and serves as a notable case study. At the end, this study seeks to contribute with recommendations for InterContinental Lisbon.